Wearable Respiratory Rate Sensor Technology for Diagnosis of Sleep Apnea - Cinel, Göktürk; Tekin, Hüseyin Cumhur; Tarım, Ergün Alperay; Tekin, Hüseyin Cumhur (IEEE, 2020)
Sleep apnea is a disease that occurs during sleep, which affects the daily life of patients due to the obstruction of the upper respiratory tract and decreases oxygen level in blood and it may even lead to patient death in the later stage. Monitoring the patients regularly has absolute importance to prevent patient disorders caused by sleep apnea. Wearable sensor technologies and patient tracking systems provide diagnosis, treatment, and monitoring of patients, and procure better health services in medical fields. In addition to decreasing the workload of health institutions, remote patient monitoring systems can serve continuous monitoring and determine variable symptoms of the patients. In this paper, we propose a patient monitoring system, which will be used for diagnosis and monitoring of sleep apnea by tracking the respiratory rate of patients with wearable sensor technology. The respiratory rate is detected using either an accelerometer sensor to be placed on the patients' abdomen or a temperature sensor to be placed on their noses. The proposed system offers an increase in the versatility of patient monitoring systems and offers an alternative new technology in sleep apnea diagnosis.
2020 Medical Technologies Congress (TIPTEKNO) -- NOV 19-20, 2020
Keywords: Sleep apnea; Respiratory rate monitoring; Wearable sensor technology